2015
DOI: 10.1128/jvi.03723-14
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Control of Simian Immunodeficiency Virus (SIV) in Cynomolgus Macaques Not Associated with Efficient SIV-Specific CD8+T-Cell Responses

Abstract: The spontaneous control of human and simian immunodeficiency viruses (HIV/SIV) is typically associated with specific major histocompatibility complex (MHC) class I alleles and efficient CD8؉ T-cell responses, but many controllers maintain viral control despite a nonprotective MHC background and weak CD8 ؉ T-cell responses. Therefore, the contribution of this response to maintaining long-term viral control remains unclear. cells are not unique contributors to the long-term maintenance of low viremia in this SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 65 publications
(93 reference statements)
6
24
0
Order By: Relevance
“…We have found that HIV-specific CD8 ϩ T cell responses in some HICs enrolled in the ANRS CO21 cohort wane over time, yet the plasma viral load remains undetectable (unpublished observations). Similar observations have been made in macaques spontaneously controlling simian immunodeficiency virus (SIV) SIVmac251 infection (10). In HICs, highly responsive CD8 ϩ T cells tend to have an effector phenotype (4,8,11), whereas weakly responsive CD8 ϩ T cells tend to have a resting memory phenotype (8,9).…”
supporting
confidence: 61%
“…We have found that HIV-specific CD8 ϩ T cell responses in some HICs enrolled in the ANRS CO21 cohort wane over time, yet the plasma viral load remains undetectable (unpublished observations). Similar observations have been made in macaques spontaneously controlling simian immunodeficiency virus (SIV) SIVmac251 infection (10). In HICs, highly responsive CD8 ϩ T cells tend to have an effector phenotype (4,8,11), whereas weakly responsive CD8 ϩ T cells tend to have a resting memory phenotype (8,9).…”
supporting
confidence: 61%
“…2 and data not shown), suggesting that the specificity of T cells in the periphery did not determine whether animals were able to prevent the replication of viruses with full-length nef sequences after intrarectal, but not intravenous, challenge. Together, these observations are consistent with data from previous studies suggesting that control of SIV replication may be independent of the CD8 T cell response, especially among animals that do not have protective MHC alleles (19,20). It is alternately possible that persistent replication of the m3KO⌬nef virus in some animals offered the maintenance of effective host immune responses, but this hypothesis is difficult to test in the small cohort of animals in this study.…”
Section: Discussionsupporting
confidence: 77%
“…Comparison of CD4:CD8 ratios in BAL of humans and macaques was confounded by the observation that DP T expressing both CD4 and CD8 were observed in BAL of macaques, but not of humans. DP T populations have been reported in multiple animal models (39)(40)(41) and in previous human studies (42)(43)(44). In humans, DP T have been described in the peripheral blood as differentiated antigen-specific cells developed in response to viral pathogens (44) and in the affected tissues of suspected autoimmune diseases (reviewed in Reference 39); DP T were also identified in BAL of HIV-infected patients with chronic obstructive pulmonary disease but not in HIV infection or chronic obstructive pulmonary disease alone (45).…”
Section: and Cd11cmentioning
confidence: 99%